2016
DOI: 10.1111/evo.13014
|View full text |Cite
|
Sign up to set email alerts
|

The maintenance of phenotypic divergence through sexual selection: An experimental study in barn swallowsHirundo rustica

Abstract: Previous studies have shown that sexual signals can rapidly diverge among closely related species. However, we lack experimental studies to demonstrate that differences in trait-associated reproductive performance maintain sexual trait differences between closely related populations, in support for a role of sexual selection in speciation. Populations of Northern Hemisphere distributed barn swallows Hirundo rustica are closely related, yet differ in two plumage-based traits: ventral color and length of the out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(54 citation statements)
references
References 75 publications
(190 reference statements)
1
53
0
Order By: Relevance
“…This apparent match between the hypothetical scenario and actual geographic variation does not deny the importance of geographic variation in female preference for each secondary sexual characteristic (e.g., plumage coloration and tail length; Safran et al 2016). Because each ornament has its own information content, some of which seems to be population-dependent (e.g., Vitousek et al 2016; also see above), female choice for each ornament should itself depend on population.…”
Section: Interrelationship Among Female Mate Preferencesmentioning
confidence: 92%
See 2 more Smart Citations
“…This apparent match between the hypothetical scenario and actual geographic variation does not deny the importance of geographic variation in female preference for each secondary sexual characteristic (e.g., plumage coloration and tail length; Safran et al 2016). Because each ornament has its own information content, some of which seems to be population-dependent (e.g., Vitousek et al 2016; also see above), female choice for each ornament should itself depend on population.…”
Section: Interrelationship Among Female Mate Preferencesmentioning
confidence: 92%
“…The target, direction, and intensity of preference varies among populations at least for plumage ornaments (e.g., Safran et al 2016;Wilkins et al 2016; reviewed in Scordato and Safran 2014;Romano et al 2017a), affecting the geographic variation in male trait expression, although most studies have found positive female preference (i.e., toward exaggerated traits; Romano et al 2017a). Well-ornamented males provide less, rather than more, paternal care compared to less-ornamented males in barn swallows (e.g., de Lope and Møller 1993;Saino and Møller 1995;Maguire and Safran 2010;Hasegawa et al 2014;Hasegawa and Arai 2015a), which may be costly for females even if wellornamented males have fewer ectoparasites and thus lower risk of contagion (Møller 1994a).…”
Section: Secondary Sexual Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…; Safran et al. ) and other characters important to avian speciation, especially vocalizations, are required to test the likelihood of these alternatives. Additionally, if secondary contact occurred but premating isolation was incomplete, hybrid incompatibilities arising due to “byproduct” genomic divergence could have precluded introgression, masking a history of secondary contact (Sobel et al.…”
Section: Discussionmentioning
confidence: 99%
“…In the control, the distant ends of the outermost tail feathers were trimmed without reducing their length (although trimming might slightly reduce tail length). We chose 11 mm because this length roughly corresponds to be aerodynamically costly part in female tails (10-12 mm: e.g., Buchanan & Evans, 2000;Rowe, Evans, & Buchanan, 2001;Cuervo & de Ayala, 2014), and recent experiments showed that a similar length (13 mm) affected mate behavior at least when manipulating male tail length (Safran et al, 2016;Vortman, Lotem, Dor, Lovette, & Safran, 2013). In addition, a 20-mm reduction (Cuervo et al, 1996) is impractical for the study population, in which the tails are shorter (78.91 ± 0.94 mm, n = 20) than European populations (84.5 ± 0.6 mm, n = 74: Cuervo et al, 1996).…”
Section: Experimental Manipulationmentioning
confidence: 99%